2016
DOI: 10.3390/math4020031
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Schrödinger Equation in the Presence of the Linear Potential

Abstract: Abstract:In this paper, we consider the time-dependent Schrödinger equation:with the Riesz space-fractional derivative of order 0 < α ≤ 2 in the presence of the linear potential V(x) = βx. The wave function to the one-dimensional Schrödinger equation in momentum space is given in closed form allowing the determination of other measurable quantities such as the mean square displacement. Analytical solutions are derived for the relevant case of α = 1, which are useable for studying the propagation of wave packet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…. Now substituting Equation (3.10) into Equation (3.5) and equating the coefficients of like powers of p, we obtain the governing equation forû 1 (k, t) as follows 11) and thus, the general equations for u j (k, t) is represented by 12) where N m û 0 (k, t) ,û 1 (k, t) , . .…”
Section: Basic Concept Of Modified Optimal Homotopy Asymptotic Methodmentioning
confidence: 99%
“…. Now substituting Equation (3.10) into Equation (3.5) and equating the coefficients of like powers of p, we obtain the governing equation forû 1 (k, t) as follows 11) and thus, the general equations for u j (k, t) is represented by 12) where N m û 0 (k, t) ,û 1 (k, t) , . .…”
Section: Basic Concept Of Modified Optimal Homotopy Asymptotic Methodmentioning
confidence: 99%
“…Now we provide stability results for the problem (5). Here we say that the goal of stability analysis of time delay problems/systems is to find the region in the delay parameter space where the considered problem/system is still stable.…”
Section: Stabilitymentioning
confidence: 99%
“…Nowadays it has become an important tool due to its wide range of applications in various scientific disciplines such as biology, chemistry, physics, dynamical systems, electrodynamics, etc. (see [1][2][3][4][5][6] and references therein). Its importance can also be explored in other fields like fluid dynamics traffic models, oscillation due to earthquakes, flow in porous media due to seepage, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different generalizations of the standard Schrödinger equation by introducing either time fractional derivatives or space fractional derivatives have been introduced for this reason [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. It has been shown that their solutions can be represented by using the Mittag-Leffler (M-L) and Fox H-functions.…”
Section: Introductionmentioning
confidence: 99%